Legends and Tales - Harte, Bret, 1836-1902 (Salt Lake City, UT : Project Gutenberg, 2006)
"Legends and Tales" by Bret Harte is a collection of short stories written during the late 19th century, primarily set against the backdrop of early Californian history. This anthology features a series of narratives that blend elements of folklore, humor, and the human experience, capturing the essence of life in the American West during a time of significant transition. Harte's tales often explore themes of adventure, morality, and the clash of cultures, using a richly descriptive style that brings the characters and their environments to life. The collection includes stories such as "The Legend of Monte del Diablo," which follows a zealous priest who encounters the devil while navigating the wilderness of California, and "The Ogress of Silver Land," a whimsical tale about princes and their dealings with a memorable ogress. Each story weaves elements of fantasy and reality, showcasing Harte$1 (Bs talent for storytelling. In "A Night at Wingdam," for instance, the author explores the lives of early settlers, delving into their struggles and the impact of civilization's advance. Throughout the anthology, Harte paints vivid images of the landscapes and people that embody the spirit of the West, making these legends a reflection of both the fantastical and the genuine aspects of American frontier life. (This is an automatically generated summary.)s
The legend of Monte del Diablo -- The adventure of Padre Vincentio -- The legend of Devil's Point -- The Devil and the broker -- The ogress of Silver Land -- The ruins of San Francisco -- A night at Wingdam.
Release date is 2006-05-22
Produced by Donald Lainson; David Widger
Keywords: Short stories; American fiction -- 19th century